Providing Breastfeeding Support During COVID-19: A Survey of Staff Experiences. (February 2022) - Hoying, Rachel; Badreldin, Nevert; Shah, Malika D.; Bolden, Janelle R.; Cummings, Peter; Robinson, Daniel T.
Background: The COVID-19 pandemic presents unique challenges to maternity settings. Its influence on providing in-hospital lactation support has not been well described. Research Aim: To describe the experiences of healthcare workers as they provided in-hospital lactation support during the pandemic. Methods: A prospective, cross-sectional, online survey evaluated healthcare providers working with postpartum women and newborns affected by COVID-19 at an academic center during March–June 2020. Providers were queried regarding the influence of COVID-19 and COVID-19-specific policies on providing lactation support. Questions assessed guidance received, perceived stress, difficulty providing care, and solicited qualitative responses. The constant comparative method was used to analyze qualitative data. Results: Of 108 providers, 70 (65%) completed the survey. Of 57 providing direct lactation support to women affected by COVID-19, most ( n = 39, 67%) reported increased stress. Participants reported lower stress scores when receiving guidance through shift meetings or email compared to those not receiving this guidance [stress score with shift meeting guidance ( M [ SD ]): 3.10 (0.88); score without guidance: 3.83 (0.66); n = 39, p = .009; score with email guidance: 3.79 (0.58); score without guidance: 4.50 (0.58); n = 18, p = .045). Qualitative responses ( n = 67; 96%) identified three themes: visitor restrictions allowed less distraction during lactation support; physical separation disrupted maternal/infant bonding; workflow challenges resulted from policy changes and supply access. Conclusions: Most participating staff providing lactation support to participants affected by COVID-19 reported increased stress. Ensuring written or verbal guidance may reduce staff's experiences of stress. Efforts to optimize lactation support during COVID-19 should consider reducing distractions, physical separation, and logistic challenges.